Abacus evolve textbook 1 (Level 3) - Merttens, Ruth (Ginn & Co; London, 2007)
The Abacus Evolve Textbooks for Year 3: * Offer clear differentiation and progression. * Contain problem-solving integrated throughout the book, including word problems, number puzzles, investigations and more. * Include 'owl questions' to extend high achievers and provide opportunities for using and applying for the whole class.